Does the Risk and Financing Structure Affect Islamic Bank Performance in Indonesia? - Ichsan Hamidi; Sulistya Rusgianto; Kamalia Sani; Robi'atul Adawiyah (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study examines the effects of Profit and Loss Sharing (PLS) financing, Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF) on the profitability of Islamic commercial banks in Indonesia. Using a quantitative approach, the study employs a fixed-effect panel data regression model based on quarterly data from five Islamic commercial banks over the 2019–2023 period. The empirical results indicate that PLS financing has a positive and statistically significant effect on profitability, while NPF exerts a negative and significant effect. In contrast, FDR shows a negative but statistically insignificant relationship with profitability. These findings suggest that Islamic bank profitability is not primarily driven by liquidity expansion or financing intensity, but rather by the quality of financing and the effectiveness of risk management. The results further highlight that profit and loss-sharing financing can function as a strategic instrument to enhance profitability when supported by strong governance and credit risk control. By integrating financing structure, liquidity behavior, and credit risk within a unified analytical framework, this study contributes to the literature by providing empirical evidence on the conditional effectiveness of Islamic risk-sharing mechanisms in an emerging Islamic banking system. Penelitian ini bertujuan untuk menganalisis pengaruh pembiayaan bagi hasil, Financing to Deposit Ratio, dan Non-Performing Financing terhadap profitabilitas bank umum syariah di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dengan model regresi data panel fixed effect berdasarkan data triwulanan dari lima bank umum syariah selama periode 2019–2023. Hasil penelitian menunjukkan bahwa pembiayaan PLS berpengaruh positif dan signifikan terhadap profitabilitas, sedangkan NPF berpengaruh negatif dan signifikan. Sementara itu, FDR memiliki pengaruh negatif namun tidak signifikan terhadap profitabilitas. Temuan ini mengindikasikan bahwa profitabilitas bank syariah tidak ditentukan oleh ekspansi likuiditas atau intensitas penyaluran pembiayaan, melainkan oleh kualitas pembiayaan dan efektivitas pengelolaan risiko. Hasil penelitian juga menegaskan bahwa pembiayaan bagi hasil dapat berfungsi sebagai instrumen strategis untuk meningkatkan profitabilitas apabila didukung oleh tata kelola yang kuat dan pengendalian risiko kredit yang memadai. Dengan mengintegrasikan struktur pembiayaan, perilaku likuiditas, dan risiko kredit dalam satu kerangka analisis, penelitian ini memberikan kontribusi empiris mengenai efektivitas bersyarat mekanisme bagi hasil dalam sistem perbankan syariah di negara berkembang.